The Eco-Villains and the end of popcorn movies - A discussion on the perception of climate activism in films and in the general debate - Bouvelot,Julie Valentine Marie (2024)
This thesis explores the perception of climate activism in films and in the general debate. By focusing on scenes in which the spectator goes through an allegiance shift towards the character of the eco-villain, I highlight a link made between the cinematographic and the non cinematographic world. My aim is to analyze the relationship between the scenes of the chosen films and the non cinematographic environment. To do so, the thesis draws upon different films starring characters of eco-villains. Theoretically departing from Audre Lorde’s postulate that “the master’s tools will never dismantle the master’s house”, I analyze the structure of power using Michel Foucault and the categorization of good and bad. I analyze what the Eco-villain represents and why it is categorized as such according to Sara Ahmed’s theory. I explore how these scenes counter this structure of power by analyzing the emotion of “anger” and the space of the heterotopia. These different theories lead me to envisage the presence of Ecocriticism theory in the different scenes. An intermedial analysis of the different visuals is used to analyze the reception of these characters and the cultural impact of fiction films on the non cinematographic world (and vice versa) in order to conclude that a major representation of climate activism is a killjoy in mass media, but these representations are challenged, countered and criticized.
Keywords: Eco-villains. Power structure. Killjoys. Climate change debate. Cinema